Farmer’s Markets as Places of Identity and Social Cohesion: A Comparative Analysis Between Monteverde and Tamarindo, Costa Rica - Zumbado Solano, Mariana (2026)
This research explores the assessments of two farmers markets in Tamarindo and Monteverde, Costa Rica, as spaces that promote identity and social cohesion. Using a quantitative approach employing in-site surveys, we analyzed the perceptions of market users regarding the contribution of the markets as spaces associated with placed identity, community identity, and social gathering spaces. Overall, the assessments were favorable in both markets, although significantly higher in Tamarindo, where there is a greater variety of products, services, and cultural activities compared to its counterpart in Monteverde. These differences favor Tamarindo considering factors such as gender, nationality, visitation frequency, and time taken to reach the market. The results suggest that these markets can promote more community cohesion and better social relations by diversifying their range of activities beyond commercial ones.